Availability modeling of terrestrial free-space-optical links using fade statistics from tropical climate - Basahel, Ahmed; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Zabidi, Suriza Ahmad (Institute of Electrical and Electronics Engineers Inc., 2018)
Free-space optical (FSO) links provide gigabit per second data rates, but its availability can easily be affected by weather conditions. FSO is a promising technology for providing high performance of wireless networking. In heavy rainfall regions, FSO links are relatively sensitive to rain. Availability prediction of FSO is indispensable part, especially in tropical areas. In this paper, empirical model is proposed to predict the availability of an FSO link ranges up to 5 km. The availability prediction model is based on long-term statistics of atmospheric attenuations under tropical climate conditions. FSO availability prediction empirical model is link distance and fade margin dependent. The proposed availability model can predict carrier as well as enterprise class availability. There is average of nearly 0.09% difference in outage between the proposed model and predicted data.